1988
DOI: 10.1113/expphysiol.1988.sp003224
|View full text |Cite
|
Sign up to set email alerts
|

Post‐translational Modification of Peptide Messengers in the Gut

Abstract: Classical methods such as precursor isolation, cell-free translation and pulse-chase experiments have been of limited use in studying biosynthesis of gastrointestinal peptides, because cell populations are generally sparse and intermingled with other cell types, rates of peptide turnover are low, and levels of mRNA are generally low. However, with the advent of recombinant DNA technology, and its application in predicting precursor sequences, the opportunity has arisen for an alternative approach to the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

1991
1991
1997
1997

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 147 publications
(206 reference statements)
0
2
2
Order By: Relevance
“…2B) which was surprising bearing in mind that G-17 normally predominates in the blood of worm-free animals (Reynolds et al 1991). This does, however, support the results of previous work cited, though not described, by Anderson et al (1988) (Dimaline, 1988); (ii) the longer half-life of G-34. In man, the half-life of G-34 is up to 8 times longer than that of G-17, depending upon the method of determination used (Nilsson, 1980), and may be further extended by sulphation (Pauwels, Dockray & Walker, 1987;Dimaline, 1988); and/or (iii) an increase in contribution made by gastrin of duodenal origin.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…2B) which was surprising bearing in mind that G-17 normally predominates in the blood of worm-free animals (Reynolds et al 1991). This does, however, support the results of previous work cited, though not described, by Anderson et al (1988) (Dimaline, 1988); (ii) the longer half-life of G-34. In man, the half-life of G-34 is up to 8 times longer than that of G-17, depending upon the method of determination used (Nilsson, 1980), and may be further extended by sulphation (Pauwels, Dockray & Walker, 1987;Dimaline, 1988); and/or (iii) an increase in contribution made by gastrin of duodenal origin.…”
Section: Discussioncontrasting
confidence: 55%
“…This does, however, support the results of previous work cited, though not described, by Anderson et al (1988) (Dimaline, 1988); (ii) the longer half-life of G-34. In man, the half-life of G-34 is up to 8 times longer than that of G-17, depending upon the method of determination used (Nilsson, 1980), and may be further extended by sulphation (Pauwels, Dockray & Walker, 1987;Dimaline, 1988); and/or (iii) an increase in contribution made by gastrin of duodenal origin. In sheep, G-34 accounts for approximately 50% of the total gastrin recovered from the last quarter of the duodenum although the total gastrin content of the latter organ is relatively small (Reynolds et al 1991 (Pearson, 1993), the magnitude of the increase in expression reported here suggests that an increase in synthesis was likely to be the main cause in the parasitized calves.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations